Perancangan Sistem Kontrol Optik Berbasis Mikrokontroler Arduino Uno R3 dengan Sensor Suara - Arfira Trisna Devi; Arif Fiansyah; Arinda Chintya Sari; Nanda Risky Maulana; Aries Saifudin; Yulianti Yulianti (Jurnal Informatika Universitas Pamulang, 2021)
In today's all-digital era, science, technology and science have brought a lot of progress in various aspects of people's lives, one of which is in the electronic field, namely electronic voice commands. The electronic voice command system can be made as a smart home control system. This system allows a person to control sound wave devices, many electronics today use only sound to use them without anyone moving, turning on or off devices, such as lights. When the user will turn on the light using sound waves, the audio sensor sends an input signal to the microcontroller and processes the microcontroller output as a voltage to turn on the load and turn on the system. When the FC0 sound sensor receives an audio input (beep code) as a clap, a value of 1 is accumulated on the Arduino and a value greater than 00mm is used as a 5V output to be turned on according to the program loaded down. When the light is on or off, the FC0 sound sensor can only provide 1s and 0s digital output signals. Adjust the sensitivity of the acoustic sensor or the noise level of the room to light a specific set of lights.